AB0772 EFFICACY OF GUSELKUMAB IN PSORIASIS PATIENTS WITH SELF-REPORTED PSORIATIC ARTHRITIS WITH INVOLVEMENT OF THE SCALP, NAILS, HANDS, AND FEET: A POOLED ANALYSIS FROM 2 PIVOTAL PHASE 3 PSORIASIS STUDIES. (June 2019) - Merola, Joseph F.; Chakravarty, Soumya D.; You, Yin; Kafka, Shelly; Karyekar, Chetan; Orbai, Ana-Maria
Abstract : Background: VOYAGE 1 & 2 were the pivotal Ph3 GUS trials for plaque psoriasis (PsO). 1, 2 Objectives: Here we compare efficacy of GUS vs PBO & vs adalimumab (ADA) on PsO involving scalp, nail & palmoplantar (palmoplantar pustular PsO excluded per protocol) in a a subgroup of pts with self-reported psoriatic arthritis (PsA), given the association between these distinct PsO phenotypes & PsA. Methods: VOYAGE 1(n=837) & VOYAGE 2(n=992) enrolled adult pts who had plaque PsO for ≥6 months, an investigator Global assessment (IGA) score ≥3, PASI score ≥12, ≥10% BSA involvement at baseline (BL), & were candidates for phototherapy or systemic treatment for PsO. Pts were randomized to GUS, PBO or aDA at BL, w/PBO crossover to GUS at wk16. This post-hoc analysis used observed pooled efficacy data for scalp-specific investigator Global assessment (ss-IGA), Physician's Global assessment (PGA) of Hands &/or Feet (hf-PGA), fingernail PGA (f-PGA), & Nail Psoriasis area & Severity index (NAPSI) in subset of pts self-reporting PsA. Results: In VOYAGE 1 & 2 combined, 335 (18.3%) PsO pts self-reported PsA (PBO 76, GUS 153, aDA 106). Baseline demographics were generally comparable across all 3 treatment grps, with history of methotrexate use: PBO 64.5%, GUS 70.6%, aDA 61.3%. A significantly greater proportion of GUS-treated pts achieved a ss-IGA score of 0/1 (absent/very mild) at wk16 vs PBO, & at wk24 vs aDA (Figure a ). Significantly higher proportions of GUS-treated pts achieved a hf-PGA score of 0/1 (clear/almost clear) vs PBO at wk16 with numerically greater differences at wk24 vs aDA (Figure B). At wk16, proportions of pts achieving a f-PGA score of 0/1 (clear/minimal) were 47.6% for GUS vs 17.0% for PBO (p<0.001). The proportions of pts achieving an f-PGA score of 0/1 for GUS vs aDA were comparable at wk16 (47.6% vs 46.4%) & wk24 (67.0% vs 60.9%), but were higher for GUS by wk48 (82.5% vs 57.5%, Table). Mean (SD)% improvement from BL in NAPSI score was significantly higher for GUS vs PBO [39.5 (48.9) vs 6.5(47.5), p<0.001] at wk16 & was comparable for GUS vs aDA at wk24 [58.0 (51.3) vs 59.9 (40.4)]. By wk48, mean% improvement from BL in NAPSI score was higher for GUS vs aDA (70.8% vs 61.3%, Table). Conclusion: GUS-treated PsO pts with self-reported PsA showed clinically meaningful improvements vs aDA in ss-IGA & hf-PGA scores at wks16 & 24. Although improvements in f-PGA & NAPSI were similar in pts treated with GUS vs. ADA at earlier timepoints, numerically greater differences were observed with GUS by wk48, likely requiring the additional duration to discriminate between treatments in this slow-growing cutaneous appendage. References: [1] Blauvelt a, et al. J am acad Dermatol. 2017Mar;76(3):405-417 [2] Reich K, et al. J am acad Dermatol.2017June;76(6): 1226 Disclosure of interests: Joseph F Merola Grant/research support from: Janssen, Soumya D Chakravarty Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson, Yin You Employee of: Employee of Janssen Research & Development, LLC, Shelly Kafka Shareholder of: J&J, Employee of: J&J, Chetan Karyekar Shareholder of: J&J, Employee of: Janssen Scientific affairs, LLC, abbott, BMS, Novartis, ana-Maria Orbai Grant/research support from: abbVie, Celgene, Horizon Pharma, Janssen, Lilly, and Novartis, Consultant for: Lilly, Janssen, Novartis, Pfizer, and UCB